Kehilangan minyak selama penyimpanan hasil olahan cassia vera=The Lost of Cassia Vera Oil from Some Dried Raw Material at Various Stage During Storage - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT Dried bark of Cinnanzomum burmannii B, known as Cassia vera in the form of 'stick', 'cut and washed' and 'broken cleaned' were stored at room temperature for 8 weeks. At various stage du 'ring storage, samples were taken for essential oil extraction. The essential oil and cinnamaldehyde contents of Cassia vera were examined. The results showed that oil content was affected by the form of raw material, but the cinnamaldehyde content was not The oil content in decreasing order were 'stick, 'cut and washed' and 'broken cleaned' samples, respectively. Total essential oil and cinnamaldehyde contents were affected by storage period. The oil content did not charge until 4 weeks storage and then decreased sharply afterwards. As the storage period increase, the cinnarnaldehyde content decreases. At 8 weeks storage period, the 'broken cleaned' samples had the lowest oil and cinnamaldehyde contents.